Efficacy and Safety of Intralesional 5-Flurouracil in Treatment of Warts - Fatima, Kaneez; Butt, Muzammal Nadeem; Javaid, Sidiqua; Noor-ul-Wara,; Bhatti, Reesham Zulkiffal; Rasheed, Rubab Ayesha (Indus Journal of Bioscience Research, 2025)
Background: Warts are common benign skin lesions caused by human papillomavirus (HPV), with varying clinical presentations based on the type of HPV and site of infection. Treatment options aim to eliminate the infected epidermis, but pain, side effects, and cost influence treatment choice. 5-Fluorouracil (5-FU), an antimetabolite, has been explored as a potential treatment, with intralesional administration offering improved efficacy over topical application. Objective: This study aimed to evaluate the efficacy and safety of intralesional 5-FU in the treatment of warts. Methods: A cross-sectional observational study was conducted between January and June 2024, enrolling 85 patients from the Dermatology Department at Pakistan Emirates Military Hospital. Intralesional 5-FU (0.1 ml/cm², 50 mg/ml) was administered biweekly, with a maximum of six injections. Patients were monitored fortnightly for two months’ post-treatment. Clinical improvement was assessed based on predefined efficacy grades: excellent (75–100% improvement), good (50–74% improvement), satisfactory (25–49% improvement), and poor (<25% improvement). Data analysis was performed using IBM-SPSS 21.0, with statistical significance set at p ≤ 0.05. Results: Of the 85 patients, 64 (75.3%) exhibited an excellent response, primarily after the second and third injections. Eleven patients (12.9%) showed a good response, six (7.1%) had a satisfactory response, and four (4.7%) demonstrated poor improvement. The treatment was well tolerated, with minor adverse effects such as erythema and oedema, and no cases of necrosis or scarring. Conclusion: Intralesional 5-FU demonstrated significant efficacy in wart treatment, with a favourable safety profile. These findings support its use as an effective alternative for managing recalcitrant warts, warranting further research to optimize treatment protocols.